PEDAGOGICAL FRAMEWORKS OF EDUCATION POLICY FOR SUSTAINABLE DEVELOPMENT OF THE EURASIAN SPACE - Zh. O. Zhilbayev; L. V. Moiseeva; M. V. Barsanova (Образование и наука)
Introduction. In the context of the widespread environmental degradation as recorded in UN documents, the issues of environmental protection are under active consideration at the international level; the measures for ensuring ecological safety are taken both within the countries and in the global space. It is possible to resolve these issues vital for further human existence only by forming ecological culture and conscientious careful attitude to the nature and environmental conditions among the population; in turn, the questions listed above could not be undertaken without fundamental re-examination of the content of education.The aims of the research presented in the publication are the following: to highlight the main directions of education policy in the Euroasian space; to define key problems of education in behalf of sustainable development of society.Methodology and research methods. Methodological framework of the research is based on the concepts of humanistic pedagogy; holistic and activity approaches to education; principles of nature conformity and co-evolution. The methods of theoretical analysis, synthesis, generalization and modeling were applied in the course of the research.Results and scientific novelty. The authors define the concept of “sustainable development of society”. The main problems that disrupt such development are identified; the main problem is that the declared statements, scientific-theoretical and scientific-practical results in the sphere of sustainable development and noospherism are in contradiction with the existing system of the industrial civilization. The philosophical and pedagogical foundations for formation of noospheric ideology among new generations as alternatives to destructive consumer anthropocentrism are briefly stated. Against this background, the common objectives of “sustainable” education development for the states of Eurasia are outlined; the conditions with an influence on its qualitative characteristics are singled out. These conditions are related to the basic principles proposed by the International Commission on Education that reflect target educational tendencies of the 21st century: “learning to know, learning to do, learning to live together, and learning to be”. It is emphasized that only the constant methodological line of development of social and economic consciousness is adherence to the principle of co-evolution – optimum ratio and coherence between co-development of elements within the triad “person-society-nature”. The institute of education is ascribed the primary role in joint creative evolutionary-gradual process as it is intended to bring up and form the identity of the responsible citizen of the Earth. The possibilities for creation of the educational ecosystem environment functioning are shown by the experience of the Republic of Kazakhstan where the Green Economy Transition (GET) is actively implemented.Practical significance. The authors’ version of an educational ecosystem structure, its way of construction and regulation are demonstrated. It is offered to use anthropo-ecocultural practices-events as educational tools.